12 Weeks of Physical Exercise Attenuates Oxidative Stress, Improves Functional Tests Performance, and Reduces Fall Risk in Elderly Women Independently on Serum 25(OH)D Concentration - Rodziewicz-Flis, Ewa Aleksandra; Kawa, Małgorzata; Flis, Damian Józef; Szaro-Truchan, Marzena; Skrobot, Wojciech Romuald; Kaczor, Jan Jacek (Frontiers in Physiology, 2022)
The study aimed to evaluate if the 25(OH)D3 concentration is related to physical training responses. Moreover, to determine the association between serum 25(OH)D3 concentration and older women’s physical performance, oxidative stress markers, inflammation, and bone metabolism. 37 older women (age 72.9 ± 5.2 years ) were assigned into two groups: supplemented (SG) and non-supplemented (NSG). Then, the participants from SG and NSG were randomly assigned into exercised and non-exercised groups: exercise sufficient vitamin D group (ESD; n=10), exercise insufficient vitamin D group (EID; n=9), control sufficient vitamin D group (CSD; n=9), and control insufficient vitamin D group (CID; n=9). To assess the study aims time up and go test (TUG), 6 minutes walk test (6MWT), fall risk test (FRT), blood osteocalcin (OC), parathormone (PTH), calcium (Ca2+), sulfhydryl groups (SH), malondialdehyde (MDA), and interleukin-6 (IL-6) were performed. The results showed that a higher 25(OH)D3 concentration was in line with better physical performance and bone metabolism as well as lower inflammation. After 12 weeks of training we noted an improvement in 6MWT (from 374.0±17.3 to 415.0±18.8; p=0.001 and from 364.8±32.8 to 419.4±32.3; p=0.001 for EID and ESD, respectively), TUG (from 7.9±0.5 to 6.8±0.8; p=0.001 and from 7.3±1.5 to 6.4±0.9; p=0.002, for EID and ESD, respectively), reduction of fall risk (from 2.8±0.8 to 1.9±0.4; p=0.003 and from 2.1±1.1 to 1.6±0.5; p=0.047, for EID and ESD, respectively) and increase in SH groups (from 0.53±0.06 to 0.58±0.08; p=0.012 and from 0.54±0.03 to 0.59±0.04; p=0.005, for EID and ESD, respectively), regardless of the baseline 25(OH)D3 concentration. However, a decrease in PTH and OC concentration was observed only in EID group (from 57.7±15.7 to 49.4±12.6; p=0.013 for PTH and from 27.9±17.2 to 18.0±6.2; p=0.004 for OC). To conclude, we found that vitamin D concentration among older women is associated with physical performance, fall risk, inflammation, and bone metabolism markers. Moreover, 12 weeks of training improved physical performance and antioxidant protection, regardless of baseline vitamin D concentration.